Robotic Training in General Surgery Residency: How Early Can We Begin? - Antonio Gangemi; Theresa Dunham; Federico Gheza; Gianmarco Contino; Pier Cristoforo Giulianotti (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Background: The increasing demand for robotics in general surgery has prompted academic institutions to train general surgery residents toward the acquisition of basic robotic skills. Our current robotic training curriculum begins in the PGY-3 year and is based on the use of surgical simulators in a risk-free environment, in which each resident must show proficiency prior to advancing to training on an animate model as PGY-4. Our unpublished data on the curriculum indicates that PGY-3s required additional remediation training on the robotic simulator, suggesting room for improvement in our teaching paradigm [8]. Because of resident duty hour restrictions, we could not provide remediation by simply increasing the number of training sessions. We therefore decided to investigate an alternative strategy of shifting the training to an earlier time point in general surgical residency during PGY-1 and PGY-2 years. To explore the feasibility of a new curriculum, we undertook a pilot study to investigate the willingness of residents in their PGY-1 and PGY-2 years to begin robotic training on the robotic simulator, the dV-Trainer (dV-T). We also wanted to see if even minimal early exposure to the dV-T would help overcome residents' initial diffidence in using the daVinci Surgical System (DaVss). Methods: Ten general surgery residents (seven PGY-1s and three PGY-2s) with no prior exposure to robotic training were randomly distributed into MIMIC (MIM G) and daVinci (DaV G) groups. The MIM G subjects answered a post-exposure questionnaire about their overall experience with the robotic training. The five MIM G subjects performed five basic skills exercises on the dV-T simulator prior to executing the same exercises on the DaVss, while the five DaV G subjects performed the same exercises only on the DaVss. Two blinded robotic proctors scored each subject's performance on the DaVss. Results: All MIM G subjects found their overall experience constructive and viewed the dV-T as useful in preparing them to complete subsequent tasks on the DaVss. The MIM G subjects also performed better than the DaV G (p= 0.32) subjects in operation of the da-Vss, although statistical significance could not be achieved. Given the small sample size, statistical significant was unlikely. Conclusions: The subjective perception of the dV-T experience was strongly positive, as the residents enjoyed the experience and seemed to be open to the possibility of introducing some robotic training with the robotic simulator earlier in their career. We attribute the fact that MIM G residents performed better with the DaVss than the DaV G residents to the value of minimal exposure to dV-T as a way to overcome the discomfort of using the DaVss for the first time.